Marginal adaptation of class V composite restorations submitted to thermal and mechanical cycling - Denise Sa Maia CASSELLI; Andre Luis FARIA-; Henrique CASSELLI; Luis Roberto Marcondes MARTINS (University of São Paulo, 2013)
Objective This study evaluated the effect of the margin location and an adhesive system on the marginal adaptation of composite restorations. Material and Methods Class V cavities were prepared in bovine teeth with the gingival margin on the dentin and the incisal margin on the enamel. The cavities were restored with a micro-hybrid composite resin using an etch-and-rinse [Single Bond 2 (SB)] or a self-etching adhesive [Clearfil SE Bond (CL)]. After finishing and polishing the restorations, epoxy replicas were prepared. The marginal adaptation was analyzed using scanning electronic microscopy (SEM, 500 x magnification). The higher gap width in each margin was recorded (T0). After the first evaluation, the samples were submitted to thermal cycling (2,000 cycles of 5°C±2°C followed by 55°C±2°C - T1) and mechanical cycling (100,000 cycles of 50 kN and 2 Hz - T2). Replicas of samples were rebuilt after each cycling and analyzed under SEM. The data were submitted to Mann-Whitney, Wilcoxon and Friedman testing (α=0.05). Results The SB presented higher gaps in the dentin than the enamel, while there was no difference between the substrate for the CL. In the dentin, the CL showed better marginal sealing than the SB. The opposite occurred in the enamel. There were no significant differences between the baseline, thermal and mechanical cycling for any experimental condition. Conclusions The outcomes of the present study showed that the adhesive system and margin location have an important effect on the marginal adaptation of composite restorations.